Factors influencing touristic consumer behaviour. Issue 3 (29th April 2021) - Santos, Vasco; Ramos, Paulo; Sousa, Bruno; Almeida, Nuno; Valeri, Marco
Abstract : Purpose: This paper aims to present a content analysis of two major constructs among tourism settings, namely involvement and emotions, strictly related to tourist behaviour, due to the fact that there are still some critical gaps in the knowledge about tourists' emotions and involvement. Design/methodology/approach: An in-depth content analysis of involvement and emotions was adopted as the methodological approach. This methodology addressed an amalgam of different definitions, frameworks, mixed theoretical and practical applications and approaches, results, comparisons as well as a blend of a set of scales of involvement and emotions by confrontating of authors. Findings: The major findings state that emotions and involvement demonstrate greater progress and scientific development to the level of tourism, marketing and consumer behaviour, representing an important issue for the integrated tourism experiences. Originality/value: This study presents a critical reflection on the importance of emotions and involvement in specific contexts of leisure and tourism.